Penggunaan Artificial Intelligence pada Pembuatan Desain Karakter Animasi - Elsa Manyori; Riyadhul Fajri; T. Rafli Abdillah (Jurnal Ilmu Komputer Aceh, 2026)
The advancement of Artificial Intelligence (AI) technology has had a significant impact across various fields, including character design in animation. This study focuses on analyzing existing systems, such as leonardo Ai, which utilize a text-to-image method to automatically generate visual design based on textual descriptions. The objective of this research is to evaluate the quality, effectiveness, and limitations of the text-to-image method in Leonardo AI for creating animated character designs that meet creative requirements. The research employs a descriptive approach using qualitative methods, involving a series of text input tests ranging from simple to complex descriptions. These tests aim to observe image quality, accuracy in representing the input descriptions and processing speed. This study provides insights into the potential and limitations of AI-based systems in the devolopment of animated character design. The findings are expected to serve as a reference for AI technology devolopers in future animation applications.